The Effectiveness of Quality and Safety Education for nurses competencies intervention to improve knoweldege ,skills and attitude of the undergraduate faculty at nursing institues: A systematic Review and Meta analysis. - Dioso, Regidor III Dioso; Naveed, Asma (Journal of University Medical & Dental College, 2024)
BACKGROUND & OBJECTIVE: Nursing education about quality and safety are a critical component of our healthcare system, and quality and safety education for nurses.QSEN competencies-based interventions have emerged as a promising approach to improveknowledge, skills, and attitudes of quality and safety. There is a need for more data to prove the effectiveness of these interventions in enhancing undergraduate nursing faculty’s competencies. The main goal of this study was to find out how well Quality and Safety Education for Nurses (QSEN)-based interventions improve the knowledge, skills, and attitudes of nursing faculty at the undergraduate level. METHODOLOGY: The researchers conducted a systematic review and meta-analysis of intervention studies that compared QSEN-based interventions with standard education or no intervention at all. The search included both published and unpublished sources from 2005 to 2022 and covered nurses, nursing students, and nursing faculty. RESULTS : Out of 6385 records, only 06 were suitable for inclusion, involving 1374 individuals. However, the results were significant. The meta-analysis showed that QSEN interventions made a big difference in the knowledge, skills, attitude, motivation, and trust of the people who took part, with a total estimate of 1.54 (0.16–2.92). The meta-analysis of variance for trial heterogeneity found a statistically significant difference, and the researchers found no evidence of publication bias. CONCLUSION: QSEN-based interventions are effective in improving the knowledge, skills, attitudes, motivation, and trust in the safety of nurses, nursing students and nursing faculty.